Inheritance and mechanism of glyphosate resistance in annual bluegrass (Poa annua L.). Issue 4 (27th December 2021) - Barua, Rajesh; Malone, Jenna; Boutsalis, Peter; Gill, Gurjeet; Preston, Christopher
Abstract: BACKGROUND: In initial screening, glyphosate was ineffective in controlling five Poa annua populations. These populations were tested for resistance, and studies undertaken to determine resistance mechanisms and inheritance pattern. RESULTS: Dose–response studies conducted at 16/12°C and 27/20°C on the five putative resistant populations showed low‐level resistance (1.4‐ to 2.5‐fold) to glyphosate. Shikimic acid accumulation in response to glyphosate confirmed differences among the populations, with greater shikimic acid accumulation in the susceptible population. The EPSPS gene copy number was 0.5‐ to 5.2‐fold greater in one resistant population (HT) than in the susceptible (S) population, but not in the others. EPSPS gene expression was five‐ to tenfold higher in HT compared with the susceptible population. Target site mutations, differences in glyphosate absorption or translocation or altered expression of aldo‐keto reductase ( AKR ) were not identified in any of the resistant populations. Crosses were successful between one resistant population and the susceptible population (P262‐16♂ ✕ S♀) and inheritance of glyphosate resistance appears to be controlled by a single, nuclear dominant gene in this population. CONCLUSION: Our study identified EPSPS gene amplification in a South Australian glyphosate‐resistant P. annua population (HT). This mechanism of resistance was not identified in the other four glyphosate‐resistant populations, and other common mechanisms were excluded. Although the resistance mechanism in some P. annua populations remains unknown, inheritance studies with one population suggest the involvement of a single dominant gene. © 2021 Society of Chemical Industry. Abstract : Glyphosate resistance was identified in five Poa annua populations, with one population displaying EPSPS gene amplification. The other populations had none of the commonly reported resistance mechanisms, suggesting multiple mechanisms are possible.